(3OaY GdXde Yf CHj GdYdGA GdeYQis - (3YeQ Hf CMeO Hf gHI Gddg Hf CHj LQGOI GdYbjdj, ceGd GdOjf GHf GdYOje,J (B660 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeI ceGd GdOjf GdMeO ddg GdcQje GdYGOd Pi GdaVd GdTGed hHYO aEfi hbaJ Ydi Ledg ef eUfaGJ CHj GdYdGA CMeO Hf YHO Gddg Hf SdjeGf ahLOJgG eTMhfI HGdaUMGI hGdHjGf s
(3BNQgG (B:s
(3cCfeG ZGfg di ef Zfi aYO Yf eYOf CShGf TQH HQZei Yf ReGf GdUHi aLdfi hbJi hCchGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B275s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B757s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI SjFI s
Keywords: (3GdCOHs